EFFECTIVENESS OF COMBINED SURGICAL PROPHYLAXIS OF LYMPHATIC COMPLICATIONS AFTER KIDNEY TRANSPLANTATION: A SINGLE-CENTER COMPARATIVE STUDY (Innovate Conferences, 2025)
Lymphatic complications following kidney transplantation, particularly lymphocele, remain a common cause of repeated interventions and prolonged hospitalization. This study evaluates the effectiveness of a combined surgical strategy aimed at preventing lymphocele formation, which includes economical dissection, targeted lymphostasis, peritonealization of the vascular bed, and elimination of the “dead space.” The application of this technique significantly reduces the incidence of clinically relevant lymphatic complications and the need for puncture procedures, shortens drainage duration and hospital stay, and does not increase the rate of early infectious complications.